IDDF2019-ABS-0174 Targeting monocyte-intrinsic enhancer reprogramming improves immunotherapy efficacy in hepatocellular carcinoma. (7th June 2019) - Liu, Man; Zhou, Jingying; Liu, Xiaoyu; Feng, Yu; Yang, Weiqin; Wu, Feng; Cheung, Otto Ka-Wing; Sun, Hanyong; Zeng, Xuezhen; Tang, Wenshu; Tsz Shun Mok, Myth; Wong, John; et al.
Abstract : Background: Hepatocellular carcinoma (HCC), mostly developed in fibrotic/cirrhotic liver, exhibits relatively low responsiveness to immune-checkpoint blockade (ICB) therapy. As myeloid-derived suppressor cell (MDSC) is pivotal for immunosuppression, we investigated its role and regulation in the fibrotic microenvironment with an aim of developing mechanism-based combination immunotherapy. Methods: Functional significance of MDSCs was evaluated by flow cytometry using two orthotopic HCC models in fibrotic liver setting via carbon tetrachloride or high-fat high-carbohydrate diet, and verified by clinical specimens. Mechanistic studies were conducted in the human hepatic stellate cell (HSC)-peripheral blood mononuclear cell culture systems and fibrotic-HCC patient-derived MDSCs. The efficacy of single or combined therapy with anti-programmed death-1-ligand-1 (anti-PD-L1) and a clinically-trialed BET bromodomain inhibitor i-BET762 was determined. Results: Accumulation of monocytic MDSCs (M-MDSCs), but not polymorphonuclear MDSCs, in fibrotic livers significantly correlated with reduced tumor-infiltrating lymphocytes (TILs) and increased tumorigenicity in both mouse models. In human HCCs, the tumor-surrounding fibrotic livers were markedly enriched with M-MDSC, with its surrogate marker CD33 significantly associated with aggressive tumor phenotypes and poor survival rates. Mechanistically, activated HSCs induced monocyte-intrinsic p38 MAPK signaling to trigger enhancer reprogramming for M-MDSC development and immunosuppression. Treatment with p38 MAPK inhibitor abrogated HSC-M-MDSC crosstalk to prevent HCC growth. Concomitant with patient-derived M-MDSC suppression by i-BET762, combined treatment with anti-PD-L1 synergistically enhanced TILs, resulting in tumor eradication and prolonged survival in the fibrotic-HCC mouse model. Conclusions: Our results signify how non-tumor intrinsic properties in the desmoplastic microenvironment can be exploited to reinstate immunosurveillance, providing readily translatable combination strategies to empower HCC immunotherapy (figure 1 ). Acknowledgement: This project is supported by the University Grants Committee through the Collaborative Research Fund (C4045–18W) and the Theme-based Research Scheme (T11–706/18-N), the Health and Medical Research Fund (16170451), the Terry Fox Foundation, the Focused Innovations Scheme-Scheme B (1907309) from the Chinese University of Hong Kong and the Li Ka Shing Foundation (Canada). Man Liu is supported by China Postdoctoral Science Foundation.